Ag3PO4/AgBr/Ag-HKUST-1-MOF composites as novel blue LED light active photocatalyst for enhanced degradation of ternary mixture of dyes in a rotating packed bed reactor - Mosleh, S.; Rahimi, M.; Ghaedi, M.; Dashtian, K.; Hajati, S.; Wang, Shaobin (Elsevier BV, 2017)
© 2017 Elsevier B.V.This study focused on a continuous flow photocatalytic rotating packed bed for simultaneous photodegradation of methylene blue (MB), auramine-O (AO) and erythrosine (ER). Blue light emitting diode strips were used as light sources in this reactor for photocatalyst activation. Ag3PO4/AgBr/Ag decorated HKUST-1 MOF composite (HKUST-1-Ag3PO4/AgBr/Ag) as novel visible light photocatalyst was synthesized and characterized by XRD, FE-SEM, EDS and DRS analyses. Eight effective parameters include initial concentrations of MB, AO and ER, rotational speed, solution flow rate, aeration flow rate, HKUST-1-Ag3PO4/AgBr/Ag mass and time of illumination were optimized using a Taguchi design L18 (21 × 37). The pH was optimized by one at a time method and fixed at 5.0. The maximum photocatalytic degradation efficacies of 92.01%, 89.57% and 89.96% for MB, ER and AO, respectively, were found at the optimum conditions: 75 min of illumination time, 15 mg/L of each dye, 0.4 g/L of HKUST-1-Ag3PO4/AgBr/Ag, 1000 rpm of rotational speed, 0.3 L/min of solution flow rate and 25 L/min of aeration rate. Kinetic study indicated that the Langmuir-Hinshelwood (L-H) model was well fitted to the experimental data of ternary photocatalytic degradation.